Earthquake Disaster Education to Students of Senior High School Using Role Playing Learning Model - Asiah, Siti; Asofi, Tuti Supriyanti; Setyowati, Dewi Liesnoor; Suharini, Erni; Hashim, Mohmadisa; Nayan, Nasir (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2023)
The aims of this study are 1) to analyze earthquake disaster education in State Senior High School 1 Karangreja, using a role-playing learning model.; 2) to analyze the knowledge and students’ attitude in dealing with earthquakes. The population of this study was all students of State Senior High School 1 Karangreja. State Senior High School 1 Karangreja is located on the slopes of Mount Slamet, making it prone to volcanic earthquakes. Disaster education for students is very needed. This will allow the students to have provisions when a disaster occurs. The number of samples is 56 respondents. The data collection techniques used are questionnaires, interviews, and documentation. The data analysis technique in this research is descriptive quantitative. The result of this study is that the condition of teachers in providing education about earthquake disasters is still at the stage of offering knowledge; there needs to be simulation practice involved. The level of preparedness knowledge of students with moderate levels of knowledge is 66% of respondents. Students with low levels of preparedness knowledge are as much as 16%. Students with an excellent preparedness attitude are as much as 52%. Researchers advise the school and the teachers to improve education on disasters, particularly earthquakes, based on the disaster vulnerability at the school.